2023
DOI: 10.1177/22799036231181845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with overweight in children under 5 years in West African countries

Abstract: Background: Overweight is a risk factor for non-communicable diseases and is affecting an increasing number of children worldwide. The objective of this study was to measure the prevalence and related factors to overweight among children under 5 years in five West African countries. Methods: This study was a secondary analysis of nationally representative cross-sectional data. These data were drawn from Demographic and Health Surveys (DHS) from five countries in the West African region (Benin, Guinea, Mali, Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…For instance, in their review, Danquah et al (2020) reported that in SSA, childhood obesity or overweight has increasingly become a public health concern. This increase was also observed in West African countries (Diallo et al, 2023).…”
Section: Introductionsupporting
confidence: 71%
“…For instance, in their review, Danquah et al (2020) reported that in SSA, childhood obesity or overweight has increasingly become a public health concern. This increase was also observed in West African countries (Diallo et al, 2023).…”
Section: Introductionsupporting
confidence: 71%